Noise channels : glitch and error in digital culture - Krapp, Peter (Electronic mediations, 2011)
To err is human; to err in digital culture is design. In the glitches, inefficiencies, and errors that ergonomics and usability engineering strive to surmount, Peter Krapp identifies creative reservoirs of computer-mediated interaction. Throughout new media cultures, he traces a resistance to the heritage of motion studies, ergonomics, and efficiency; in doing so, he shows how creativity is stirred within the networks of digital culture. Noise Channels offers a fresh look at hypertext and tactical media, tunes into laptop music, and situates the emergent forms of computer gaming and machinima.